Efficacy of A Poly(MeOEGMA) Brush on the Prevention of Escherichia coli Biofilm Formation and Susceptibility - Patrícia Alves; Luciana Calheiros Gomes; Cesar Rodríguez-Emmenegger; Filipe José Mergulhão (MDPI AG, 2020)
Urinary tract infections are one of the most common hospital-acquired infections, and they are often associated with biofilm formation in indwelling medical devices such as catheters and stents. This study aims to investigate the antibiofilm performance of a polymer brush-poly[oligo(ethylene glycol) methyl ether methacrylate], poly(MeOEGMA)-and evaluate its effect on the antimicrobial susceptibility of Escherichia coli biofilms formed on that surface. Biofilms were formed in a parallel plate flow chamber (PPFC) for 24 h under the hydrodynamic conditions prevailing in urinary catheters and stents and challenged with ampicillin. Results obtained with the brush were compared to those obtained with two control surfaces, polydimethylsiloxane (PDMS) and glass. The polymer brush reduced by 57% the surface area covered by E. coli after 24 h, as well as the number of total adhered cells. The antibiotic treatment potentiated cell death and removal, and the total cell number was reduced by 88%. Biofilms adapted their architecture, and cell morphology changed to a more elongated form during that period. This work suggests that the poly(MeOEGMA) brush has potential to prevent bacterial adhesion in urinary tract devices like ureteral stents and catheters, as well as in eradicating biofilms developed in these biomedical devices.